Empathetic reflection: reflecting with emotion. Issue 4 (4th July 2021) - Marathe, Abha; Sen, Archana
ABSTRACT: Reflection, an action in retrospect, is a purposeful action of thinking and drawing meaning from it. Since thinking has content component and an emotion component, reflection involves paying attention to both the content and the emotion component. Focusing on the content and emotion of self during reflection increases the lessons learnt from reflection and makes the reflective process meaningful. However, focusing on the content and emotion experienced by others involved in the event makes it empathetic. Empathetic reflection is when the reflector acknowledges the emotion of others involved in the event along with the emotion of self. This reflective journey may require the reflector to take lessons in being emotionally intelligent either by self-monitoring or by working on scaffolding provided by people more knowledgeable of the reflective process. In the field of education, empathetic reflection will enable the teacher to build a better student teacher relationship, and also have an unbiased, critical and holistic understanding of the situation.